Investigation of the ultrashort pulsed laser processing of zinc at 515 nm: Morphology, crystallography and ablation threshold. (5th May 2019) - Mustafa, H.; Matthews, D.T.A.; Römer, G.R.B.E.
Abstract: Bulk polycrystalline pure zinc is ablated in air using a picosecond laser source to perform single pulse and multi-pulse processing at a wavelength of 515 nm. The geometries and surface morphologies of the resulting craters are determined by confocal laser scanning microscopy and scanning electron microscopy. Further, the ablation threshold and its corresponding incubation coefficient is determined from the ablated volume for multiple laser pulses. Two different thermal ablation regimes are identified. The single pulse ablation thresholds are found to equal 0.1 J/cm 2 and 0.68 J/cm 2 respectively for the two regimes. It is found that the incubation coefficients are larger than unity, indicating material removal becomes energy expensive for multiple pulse laser irradiation. It is also found that an irradiated area undergoes laser induced preferred crystal orientation. Graphical Abstract: Unlabelled Image Highlights: For picosecond pulsed laser processing of Zn, material removal occurs by thermal ablation. Two morphologically-distinct ablation regimes are found, partitioned at a fluence level of 10 J/cm 2 . Laser processing of polycrystalline zinc at 515 nm with a picosecond laser source leads to laser induced preferential crystal orientation (LIPCO).